Unequal Lives : Gender, Race and Class in the Western Pacific - Alexeyeff, Kalissa; Bainton, Nicholas A.; Cox, John; McDougall, Debra; Alexeyeff, Kalissa; Bainton, Nicholas A.; Cox, John; McDougall, Debra (Canberra ANU Press, 2021)
As we move further into the twenty-first century, we are witnessing both the global extensification and local intensification of inequality. Unequal Lives deals with the particular dilemmas of inequality in the Western Pacific. The authors focus on four dimensions of inequality: the familiar triad of gender, race and class, and the often-neglected dimension of generation. Grounded in meticulous long-term ethnographic enquiry and deep awareness of the historical contingency of these configurations of inequality, this volume illustrates the multidimensional, multiscale and epistemic nature of contemporary inequality. This collection is a major contribution to academic and political debates about the perverse effects of inequality, which now ranks among the greatest challenges of our time. The inspiration for this volume derives from the breadth and depth of Martha Macintyre's remarkable scholarship. The contributors celebrate Macintyre$1 (Bs groundbreaking work, which exemplifies the explanatory power, ethical force and pragmatism that ensures the relevance of anthropological research to the lives of others and to understanding the global condition.s
English
Keywords: Australasian & Pacific history; Social issues & processes; Ethical issues & debates; Social groups; Social & cultural anthropology, ethnography; Inequality; Martha Macintyre; Melanesia; Gender; Race; Class; Western Pacific